An Analysis of the Use of Multiple Languages Among Sellers at Mangli Market, Jember, to Maintain Positive Transactional Interactions with Their Buyers in 2004 - Dwi Puspitarini (Fenomena, 2006)
Multilingualism in traditional markets creates communication challenges between sellers and buyers from different ethnic and social backgrounds. This study aims to describe language use, the influence of social status, and sellers' strategies for maintaining effective transactional interactions in Pasar Mangli, Jember. Using a descriptive-qualitative approach with purposive sampling, data were collected through observation, questionnaires, and interviews with 200 sellers. The findings reveal that three languages are used: Javanese, Madurese, and Indonesian. Social status significantly influences language choice, with large sellers tending to master all three languages and using code-switching as their main strategy, while small sellers have more limited proficiency. The most effective strategy is switching to the buyer's language. This study recommends integrating an understanding of code-switching into communication training for traders in multiethnic markets. Fenomena multilingualisme di pasar tradisional menciptakan tantangan komunikasi antara penjual dan pembeli yang berasal dari latar belakang etnis dan sosial berbeda. Penelitian ini bertujuan mendeskripsikan penggunaan bahasa, pengaruh status sosial, dan strategi penjual dalam menjaga interaksi transaksional yang baik di Pasar Mangli, Jember. Menggunakan pendekatan deskriptif-kualitatif dengan teknik purposive sampling, data dikumpulkan melalui observasi, kuesioner, dan wawancara terhadap 200 penjual. Hasil penelitian menunjukkan bahwa terdapat tiga bahasa yang digunakan: Bahasa Jawa, Bahasa Madura, dan Bahasa Indonesia. Status sosial sangat memengaruhi pilihan bahasa, di mana penjual besar cenderung menguasai ketiga bahasa dan menggunakan alih kode sebagai strategi utama, sementara penjual kecil lebih terbatas kemampuannya. Strategi yang paling efektif adalah beralih ke bahasa pembeli. Penelitian ini merekomendasikan pentingnya pemahaman alih kode dalam pelatihan komunikasi bagi pedagang di pasar multietnis.